Performance, Gut Size and Ileal Digesta Viscosity of Broiler Chickens Fed with a Whole Wheat Added Diet and the Diets with Different Wheat Particle Sizes - Odunsi, A.A. (International Journal of Poultry Science, 2002)
To evaluate the effect of various particle sizes of wheat grain in meat-type birds, the performance and gut response of birds to 4 starter diets containing 30% and 4 finisher diets containing 50% wheat grain of different particle sizes passed through 4, 5, 6 and 7 mm sieves were compared with the responses of birds to whole wheat addition in a starter and a finisher diet at the same rates. The dietary treatments were as follows: fine texture (F) for wheat sieved by 4 mm, medium texture 1 (M1) for 5 mm sieved wheat, medium texture 2 (M2) for 6 mm sieved wheat, coarse texture (C) for 7 mm sieved wheat and whole (W) for whole wheat. All diets were isocaloric and isonitrogenous, and all other main dietary ingredients except wheat were ground to pass 5 mm sieve. The performance parameters were feed intake, weight gain and feed conversion ratio from 0 to 42 d. In vivo viscosity of ileal digesta, fresh lengths and weights of whole digestive tract and the amount of abdominal fat were also determined for all treatments. The results revealed that the best performance was obtained from the C diets, the F diet resulted in the lowest performance and those resulting from the M1, M2 and W were intermediate. However, the worsened performance induced by F and W starter diets of 30% wheat up to 21 d old was statistically become insignificant at later ages with finishing diets of 50% in comparison with the M1, M2 and C diets, suggesting that particle size of wheat grain lead to significant changes in bird`s performance at early starting and growing periods, but not during the finishing periods even though the rate of wheat in the diet was increased from 30 to 50%. The diet of fine wheat particle resulted in significantly higher ileal digesta viscosity than the coarse and whole wheat added diets at both 21 d and 42 d old. It is most likely that increased digesta viscosity and changes in gut size can induce significant changes in the performance of broiler chickens, especially when the birds were young. In short, feeding broiler chickens with fine texture of wheat grain at early growing periods is not suggested due to the increased ileal viscosity and depressed performance although the negative effects of fine texture of wheat grain were overcome during finishing period even with 50% wheat additions. Medium and coarse texture of wheat grain remained to be the most preferred form of cereal grains although the whole grain is of great importance when no cost is considered for grinding.